An introduction to the Geodynamic Evolution of the Southernmost Andes: Connections with the Scotia Arc - Ghiglione, Matias
The backbone of this book is the analysis of the relation between the tectonic evolution of the Southernmost Andes and its southern neighbors: Antarctica and the Scotia Sea. The Southernmost Andes comprise the southern bent of the Andean mountains, where they progressively change their strike from the N-S?oriented Southern Patagonian Andes to the E-W?trending Fuegian Andes (Fig. 1). These Andean segments and their corresponding basement, sedimentary basins, magmatic rocks and batholithic belts are linked, even if sometimes elusively, to the evolution of the Antarctic Peninsula and of the islands spread in the southern ocean. The Scotia Sea separating South America and the Antarctic Pe-ninsula (Fig. 1) is only ~30 Myr old, very young, considering a joint geological history of the Southernmost Andes, Patagonia and Antarctica than can be traced back to late Paleozoic times (i.e. 300 Myr or more). Analysis of marine geophysical data in the Scotia Sea (cf. Eagles et al. 2006) and geological data from Tierra del Fuego (Ghiglione et al. 2008) demonstrate that the disconnection of South America and Antarctica started at about 50 Ma. However, oceanic spreading producing the final opening of the Drake Passage, and the consequent strike-slip movements along the North and South Scotia ridges (Fig. 1), occurred just since the Oligocene. Therefore, there is a joint history of Antarctica and South America that was shattered by the opening of the Scotia Sea; the remaining pieces of the puzzle, how can they fit together, and how were they separated from each other are the subjects of this book. Fil: Ghiglione, Matias. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Estudios Andinos "Don Pablo Groeber". Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Estudios Andinos "Don Pablo Groeber"; Argentina